Estimating the underground economy by using MIMIC models: A response to T. Breusch's critique - Roberto Dell'Anno; Friedrich G. Schneider (Johannes Kepler University of Linz, Department of Economics, 2006)
Breusch (2005b) critically addresses an important and challenging question: Is it reliable to use the Multiple Indicators Multiple Causes model to estimate Shadow Economy? Breusch concludes that this approach is not suitable for the purpose. Breusch's paper highlights the different procedures and hypotheses about the estimation of the size and development of the shadow economy in three papers: Giles and Tedds (2002a), Dell'Anno and Schneider (2003) and Bajada and Schneider (2005). In this paper, we will react and provide some answers to Breusch's criticisms with special reference to the criticisms of the Dell'Anno and Schneider (2003) paper. According with us, the MIMIC model is still one of the best approaches to this purpose.
Keywords: 330; shadow economy; MIMIC model; structural modelling.; Schattenwirtschaft; Wirtschaftsmodell; Kritik; Theorie